Foot Massage Influences Circulation Fluctuations in the Event of Chronic Failure Edema of the Foot - Nugroho, Nehru; Annisa, Rahma; Sahran, Sahran (Baiman Bauntung Batuah Center, 2024)
Chronic Kidney Disease (CKD) is an irreversible kidney condition. One of the clinical symptoms of CKD is leg edema, which, if left untreated, causes discomfort, immobility, risk of falling, and skin problems. Foot edema in CKD patients can be alleviated using both pharmaceutical and non-pharmacological treatments, one of which is foot massage. The study aimed to investigate the effect of foot massage on the circumference of leg edema in CKD patients. It used quantitative methodologies with a quasi-experimental design for one group pretest-posttest. The sampling method employed was purposive sampling. A sample of 18 persons was taken from the Hemodialysis unit of RSUD Dr. M. Yunus Bengkulu. The data collection strategy consisted of documenting the results of measuring the circumference of leg edema using Medline before and after the intervention, which was carried out for 20 minutes on both legs over three days. Data will be evaluated univariately and bivariately with the Paired Test to determine the effect of foot massage on leg edema. The study found that 72.2% of respondents were female, and the average circumference of left leg edema before and after intervention was 21.66 cm and 21.02 cm, respectively. The average circumference of right leg edema before and after intervention was 21.74 and 21.07 cm. The study found that foot massage significantly influenced the circumference of leg edema before and after the intervention, with a P value of 0.000 (P<0.005) for both legs. The study's findings can be used by nurses to guide nursing interventions/actions, particularly for CKD patients with posthemodialysis edema.